(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
Тhe period of maturity is called the "Golden" period of personality development, characterized by progressive changes and the peak of creative productivity. Some scientists call the crisis of forty years the most dangerous period of maturity. This article highlights the understanding of the concept of "crisis of forty years" in the concepts of various researchers, as well as the causes and symptoms of the crisis in men and women. In the event of a crisis of 40 years, a person has to once again rebuild his life plan, to develop a largely new "I"-the concept. This crisis can be associated with serious changes in life, up to the change of profession and the creation of a new family.